Exporting a Constitutional Court to Brunei? Benefits and Prospects - Ann Black (Constitutional Review, 2022)
Negara Brunei Darussalam (Brunei) is Asia’s only, and one of the world’s few remaining, absolute monarchies. Brunei’s much-venerated Sultan and Yang Di Pertuan Agong is accountable to only Allah as his “shadow on earth”. Within the Sultanate he is head of religion, Prime Minister, and as Sultan he appoints all members to the nation’s six advisory Councils. He is above the law and is the country’s legislator. He can amend the constitution and bypass the Legislative Council without court oversight. Judicial review was formally abolished in 2004. The accrual of power – judicial, religious, legislative, and executive – in the hands of one man is only possible by the continued renewal of a state of emergency. Since 1962, the state of emergency has been renewed every two years and once Brunei is in a state of emergency, all powers devolve to its Sultan. There is an absence of any effective checks and balances mechanism such as a democratically elected Legislative Council, a free and open media, a judiciary with powers of constitutional review, an accountable executive government, or an engaged civil society. Because the constitutionality of sixty years of emergency rule in Brunei has never been judicially determined, this paper argues it would be the first task for an independent Constitutional Court. The need for such determination on the legitimacy of Brunei’s biennial emergency proclamations is set out and a case made as to why a Constitutional Court could be the circuit breaker for a return democratic participation, rule of law, and fundamental human rights in the Sultanate. There is reflection on the obstacles to any reform which make the prospects for this unlikely in the lifetime of the current Sultan.